Chemical Genetic Screen Identifies Natural Products that Modulate Centriole Number. (23rd September 2016) - Graciotti, Michele; Fang, Zhou; Johnsson, Kai; Gönczy, Pierre
Abstract: Centrioles are microtubule‐based organelles found in most eukaryotic cells and that are critical for the formation of cilia and flagella, as well as of centrosomes in animal cells. The number of centrioles must be strictly regulated in proliferating cells in order to ensure genome integrity upon cell division. Despite their importance, however, the mechanisms governing centriole assembly and number control remain incompletely understood, owing in part to a paucity of available small‐molecule compounds for dissection and alteration of the underlying processes. Here we have developed a chemical genetic approach to identify small‐molecule compounds capable of modulating centriole numbers in human cells. High‐throughput screening of ≈2600 natural compounds identified 14 candidate molecules that either diminish (ten compounds) or augment (four compounds) the number of centrioles per cell. We investigated the mechanisms of action of four of these compounds and discovered that two of them potentially reduce centriole number through effects on NF‐κB signalling. Moreover, we established that one further compound blocks cell cycle progression and probably indirectly causes an augmentation of centriole number. The last compound analysed induces, in addition to excess centrioles, exceptionally long primary cilia‐like structures. Overall, our analysis demonstrates that natural products constitute a rich source of tool compounds useful for unravelling and manipulating the mechanisms governing centriole assembly and number control. Abstract : When in doubt, go to the library : We present a chemical high‐throughput screening of a natural product library directed towards the identification of chemical scaffolds capable of altering centriole numbers in cycling cells. Centrioles are microtubule‐based structures essential for the formation of cilia and flagella. Centriole aberration is involved in ciliopathies and carcinogenesis.